THE SIGNIFICANCE OF ENVIRONMENTAL EDUCATION IN THE CONTEXT OF INCREASING ENVIRONMENTAL ISSUES OF SOCIETY - Lucia Kováčová (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The study brings an assessment of the significance of environmental education as one of the means of ensuring protecting of the environment. Environmental education is continually gaining importance due to the newly emerged environmental issues in society, particularly those with severe impact. One of the main goals of this study is to consider serious environmental issues of society and then analyse the significance of education in this area, as well as to classify ongoing forms of study programmes in particular stages of the educational system in The Slovak Republic.